Efficient determination of fish spoilage using colorimetric strips from sugarcane bagasse waste - Syed Gazanfar Abbas; Fatima Sherazi; Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Faryal Aftab; Shamroza Mubarik; Muhammad Imran Khan; Abdallah Shanableh; Rafael Luque (Results in Engineering)
The preparation of colorimetric strips from biomass is an emerging technology for the conversion of waste into valuable products. In the present study, colorimetric strips were prepared from sugarcane waste and coated with three different dye solutions including Bromophenol blue, Bromocresol green, and Erichrome black-T. Infrared Spectroscopy (IR) and Scanning Electron Microscopy (SEM) were employed to evaluate structural and morphological characteristics of strips with and without dye coatings. The response time and effectiveness of colorimetric strips were accessed by their reaction with Trimethylamine (TMA), produced by spoiled fish. The shift in absorbance was observed by Visible Spectroscopy and the color change was confirmed by the interaction of dyes with TMA. To validate the colorimetric strips TMA levels in spoiled fish were quantified by steam distillation and titration with 0.1 N HCl. The limit of detection of Bromophenol Blue, Bromocresol Green, and Eriochrome Black-T was ∼10.009, ∼6.38, and ∼6.33 mg l-1 respectively. The monitoring of fish spoilage by colorimetric strips is simple, cost-effective, and eliminates the need for expensive equipment, trained personnel, or extensive sample preparation, resulting it an ideal approach for real-time, on-site assessments.